2021
DOI: 10.1016/j.ogla.2020.10.008
|View full text |Cite
|
Sign up to set email alerts
|

OCT Signal Enhancement with Deep Learning

Abstract: Purpose: To establish whether deep learning methods are able to improve the signal-to-noise ratio of time-domain (TD) optical coherence tomography (OCT) images to approach that of spectral-domain (SD) OCT. Design: Method agreement study and progression-detection in a randomized, double-masked, placebo-controlled, multi-centre trial for open-angle glaucoma (OAG) [UK Glaucoma Treatment Study (UKGTS)]. Participants: Cohort for training and validation: 77 stable OAG participants with TDOCT and SDOCT imaging at up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Recently, generative adversarial networks (GANs) 9 have been extensively used in the artificial intelligence community for the synthesis of artificial images and have emerged as a potential technique to address the challenge of data scarcity in biomedical applications. 10 In ophthalmic studies, GAN models have been demonstrated in segmentation, [11][12][13][14] data augmentation, [15][16][17][18][19] domain transfer, [20][21][22] image enhancement, [23][24][25][26] and others. 27 In data augmentation with GANs, prior studies on synthetic fundus 15,28,29 and optical coherence tomography (OCT) image generation 16,30 have largely focused on retinal disorders, which are assessed by the presence of lesions.…”
mentioning
confidence: 99%
“…Recently, generative adversarial networks (GANs) 9 have been extensively used in the artificial intelligence community for the synthesis of artificial images and have emerged as a potential technique to address the challenge of data scarcity in biomedical applications. 10 In ophthalmic studies, GAN models have been demonstrated in segmentation, [11][12][13][14] data augmentation, [15][16][17][18][19] domain transfer, [20][21][22] image enhancement, [23][24][25][26] and others. 27 In data augmentation with GANs, prior studies on synthetic fundus 15,28,29 and optical coherence tomography (OCT) image generation 16,30 have largely focused on retinal disorders, which are assessed by the presence of lesions.…”
mentioning
confidence: 99%
“…The fundus autofluorescence images were generated from en-face OCT images using GAN to identify the geographic atrophy region Tavakkoli et al [ 62 ] Conditional GAN Fundus photography → Fluorescein angiography The proposed GAN produced anatomically accurate fluorescein angiography images that were indistinguishable from real angiograms Yoo et al [ 63 ] CycleGAN Ultra-widefield fundus photography → Fundus photography Ultra-widefield images were successfully translated into traditional fundus photography-style images by CycleGAN, and the main structural information of the retina and optic nerve was retained Ju et al [ 64 ] CycleGAN Fundus photography → Ultra-widefield fundus photography The CycleGAN model transferred the color fundus photographs to ultra-widefield images to introduce additional data for existing limited ultra-widefield images. The proposed method was adopted for diabetic retinopathy grading and lesion detection Lazaridis et al [ 91 , 108 ] Wasserstein GAN + perceptual loss (conditional GAN) Time-domain OCT → spectral-domain OCT Time-domain OCT was converted to synthetic spectral-domain OCT using GAN. The model improved the statistical power of the measurements when compared with those derived from the original OCT GAN = generative adversarial network; OCT = optical coherence tomography …”
Section: Reviewmentioning
confidence: 99%
“…For image segmentation, GANs have been used to enhance retinal vessel [166][167][168] and corneal nerves segmentation [169]. GANs have also been applied to perform denoizing, enhancement and super-resolution in ophthalmic imaging, on OCT [170][171][172][173][174][175], fundus photography [176][177], and dehazing of cataractous retinal images [178]. In sum, GAN-driven image synthesis can greatly boost DL-based detection and diagnosis of diseases.…”
Section: Generative Adversarial Networkmentioning
confidence: 99%